Sustainable development in OECD countries getting the policies right - Herd, Richard; Cournede, Boris; Sutherland, Douglas (Organisation for Economic Co-operation and Development, 2004)
This publication summarizes the lessons learned from the 30 country reviews of sustainable development that have been published since 2002 as part of OECD economic surveys. It also examines the concrete action that countries have taken to promote sustainable development while concentrating on the results that have been achieved and the efficiency of achieving the results. The publication focuses on major policy areas including the improvement of environmental policies, raising living standards in developing countries, and ensuring sustainable retirement income policies. Numerous tables provide detailed data and sustainable development indicators that have been used to gauge performance and assess costs.--Publisher's description.
Keywords: OECD; Nachhaltige Entwicklung / Entwicklungshilfe / Internationale Umweltpolitik / Umweltpolitik / Wirtschaftspolitische Wirkungsanalyse / OECD-Staaten; Entwicklungsländer; Nachhaltigkeit; Wirtschaftspolitik; Desarrollo sostenible -- Países de la OCDE; Duurzame ontwikkeling.; Sustainable development -- Developing countries; Geschichte; Umweltschutz; Developing countries -- Economic policy; Países de la OCDE -- Política económica